2019
DOI: 10.1136/oemed-2018-105408
|View full text |Cite
|
Sign up to set email alerts
|

Cross-national comparison of two general population job exposure matrices for physical work exposures

Abstract: ObjectivesJob exposure matrices (JEMs) are increasingly used to estimate physical workplace exposures. We conducted a cross-national comparison of exposure estimates from two general population JEMs to aid the interpretation of exposure–outcome associations across countries and to explore the feasibility of cross-national application of JEMs to provide workplace physical exposure estimates.MethodsWe compared physical exposure estimates from two general population JEMs created from the FrenchCohorte des consult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 20 publications
2
22
1
Order By: Relevance
“…Unlike self‐reported data, a JEM can also be applied retroactively to assign past exposures based on job titles that can then be used to study current or future chronic diseases . There is potential in using JEMs outside their countries of origin or to complement existing JEMs that might lack particular exposures; recently, we found that physical exposure estimates from this French JEM can be applied to an American JEM, and vice versa . However, further cross‐national comparisons are needed to fully realize this rapidly expanding area of occupational epidemiology research …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike self‐reported data, a JEM can also be applied retroactively to assign past exposures based on job titles that can then be used to study current or future chronic diseases . There is potential in using JEMs outside their countries of origin or to complement existing JEMs that might lack particular exposures; recently, we found that physical exposure estimates from this French JEM can be applied to an American JEM, and vice versa . However, further cross‐national comparisons are needed to fully realize this rapidly expanding area of occupational epidemiology research …”
Section: Discussionmentioning
confidence: 99%
“…Recently, we constructed a general population JEM from self‐reported physical work exposures in a large general population cohort study of salaried workers in France (Cohorte des consultants des Centres d'examens de santé—CONSTANCES) . In our previous studies, we found that this CONSTANCES JEM created homogenous exposure groups that could discriminate physical work exposures between different jobs, and that there was substantial agreement between this French JEM and an existing American JEM . To further validate the CONSTANCES JEM, this study tested the ability of the CONSTANCES JEM to demonstrate known exposure‐outcome associations for MSD symptoms at multiple body locations by applying the JEM to a new sample of participants (validation sample) from the same cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of job demands, pertaining to the frequency and intensity, were provided by expert job analysts and from self-reported exposures by individual workers across different jobs. Job demands in O*NET were scored on a 5-or 8-point ordinal scale with exposure-specific descriptive anchors (16). Occupations from O*NET were assigned a standard occupational classification (SOC) job code.…”
Section: Individual-level Measuresmentioning
confidence: 99%
“…Two raters, blinded by case status, assigned job codes independently, with differences resolved by consensus. For assigning exposure values using the CONSTANCES JEM, we created a crosswalk to match French PCS codes with American SOC codes based on similarity of work physical exposures (16). French PCS codes were first matched to three-digit ISCO-88 (International Standard Classification of Occupations) codes using the Codage Assisté des Professions et Secteurs d'activité (CAPS) and an existing French auto-coding tool (24).…”
Section: Assigning Jem Exposure Estimates To Individual Workersmentioning
confidence: 99%
See 1 more Smart Citation